Influencia histórica del liberalismo en el magisterio pontificio decimonónico sobre libertad religiosa: ¿continuidad o ruptura con el Vaticano II? - Jorge Salinas Mengual (Vergentis. Revista de Investigación de la Cátedra Internacional Conjunta Inocencio III, 2019)
The right to religious freedom has been the object of an historical evolution in the definition of its content, which has not only been affected by the relations between temporal and spiritual power, but also by the influence of ideologies that have tried to circumscribe religion to the merely private field, in an attempt to build a new society that identifies the progress of man in the development of science and in neglecting God. One of these ideologies, liberalism, has had a very important role in the definition of the guidelines of the right to religious freedom by the Magisterium of the Church. This article analyses the modality in which the following three Popes of the 19th century interpreted this right: Gregory XVI, Pius IX and Leo XIII; it analyses the aspects on which they put more attention, the extent to which liberalism influenced the development of their theory on this topic and the extent to which we can talk about continuity or rupture in the history of the ecclesial Magisterium in relation to the definition of the right to religious freedom, especially in the context of the Declaration Dignitatis humanae of the Second Vatican Council.